(untitled) (Journal of the College of Basic Education, 2023)
Geopolitics is defined by some as a synonym for applied geopolitics, i.e.In the sense of national policy affected by the natural environment, especially when that country emphasizesNational security or foreign policy (1) because geopolitics is directly related to the science thatIt is concerned with the study of the geographic location of the people or their locations, especially in their behavior.The diplomatic issue of the state (2) It is also based on studying the natural situation of the state in terms ofits claims in the field of international politics. While the geopolitical task is limited toExamination and study of the ground field. Thus, geopolitics means the philosophy of the strength of the site.And its impact on the political history of the country and on the entirety of its internal conditions and on its behavior.diplomacy and its future plans to preserve its identity and territorial sovereignty, and what this requiresforeign policies that determine the nature of the political behavior of this or that country in line withSite Requirements Yemen is distinguished by its distinguished geopolitical location among the countries of the region and the world.It oversees the southern entrance to the Red Sea, the Gulf of Aden and the Arabian Sea, in addition toto its climatic distinction, agricultural wealth, and commercial connections, which were a natural resultFor this site and in order for the research to be diversified in its methods and to achieve its desired goal, it wasThe use of most geographical approaches, whether the morphological, descriptive or analytical approaches.In addition to the historical curriculum.